2014
DOI: 10.1159/000368799
|View full text |Cite
|
Sign up to set email alerts
|

Does the Aberrant Expression of CD2 and CD25 by Skin Mast Cells Truly Correlate with Systemic Involvement in Patients Presenting with Mastocytosis in the Skin?

Abstract: Although sMCs displayed immunoreactivity for one of the neoplastic antigens in the majority of SM patients, the aberrant CD2 and/or CD25 expression on sMCs is not as indicative of SM as the BMMC immunophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
13
3
Order By: Relevance
“…The differential diagnosis for CM includes xanthogranuloma, leukemia cutis, metastasis, vascular tumors, adnexal tumors and melanocytic tumors . Cutaneous mastocytosis is diagnosed on the basis of a typical skin lesion morphology, a positive Darier sign, histopathology and the absence of systemic mastocytosis (SM) criteria . An extension study should include blood cell count, serum chemistries (including liver function tests), serum tryptase levels and bone marrow biopsy (to evaluate mast cell clusters, morphology, immunophenotype and KIT gene mutation) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis for CM includes xanthogranuloma, leukemia cutis, metastasis, vascular tumors, adnexal tumors and melanocytic tumors . Cutaneous mastocytosis is diagnosed on the basis of a typical skin lesion morphology, a positive Darier sign, histopathology and the absence of systemic mastocytosis (SM) criteria . An extension study should include blood cell count, serum chemistries (including liver function tests), serum tryptase levels and bone marrow biopsy (to evaluate mast cell clusters, morphology, immunophenotype and KIT gene mutation) …”
Section: Discussionmentioning
confidence: 99%
“…In fact, while CD25 expression is highly suggestive of SM in patients with urticaria pigmentosa, it is a minor criterion for SM . Despite this evidence, Lange et al concluded that, even though skin mast cells display immunoreactivity for CD25 in most SM patients, aberrant expression of this antigen in skin mast cells is not as indicative of SM as would be its expression in bone marrow mast cells. In the case of our patient, however, the combination of strong CD25 positivity and marked pleomorphic mast cells was highly suggestive of systemic involvement, for which reason a bone marrow biopsy was performed to rule out malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] When involving the skin, neoplastic mast cells tend to have normal cytological features and do not differ from reactive mast cells; hence, we currently lack a specific marker for neoplastic mast cells in the skin, 13,14 in contrast with the well-known marker CD25 for neoplastic cells in the bone marrow. [15][16][17][18][19][20] Although several studies have shown that CD25 expression by mast cells in the skin was predictive of SM, [21][22][23] this immunostaining may not be applicable to CM. In fact, it has been shown that CD25 expression in the skin is not a reliable marker.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that CD25 expression in the skin is not a reliable marker. 23,24 Hence, in cases with very few neoplastic mast cells, the diagnosis is solely based on poorly defined, additional signs: the mast cell count (with different suggested cut-off values) [25][26][27][28][29][30] and other signs: (i) hyperpigmentation of the basal layer of the epidermis, (ii) dilated, more numerous blood vessels in the upper dermis, (iii) the presence of eosinophils, or (iv) fibrosis. 6,31 The diagnosis of challenging cases of CM or of skin involvement in SM therefore requires more reliable signs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also showed a positive correlation between the density of CD117 and CD25 positive mast cells in the skin infiltrates of systemic mastocytosis patients and the lack of a similar correlation in the skin of cutaneous mastocytosis patients. However, their conclusion is that the bone marrow mast‐cells immunophenotype is more specific for systemic mastocytosis than CD2 and/or CD25 expression on skin mast cells …”
Section: Discussionmentioning
confidence: 99%